1994
DOI: 10.1159/000310457
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Contamination during Extracapsular Cataract Extraction

Abstract: Postoperative endophthalmitis remains one of the most devastating complications of eye surgery. In recent years infections with so called ‘nonpathogenic’ organisms like Propionibacteriumacnes or coagulase-negative staphylococci have gained in importance. 200 patients were included in this study, from whom preoperative smears of the conjunctiva and intraoperative aspirates of the anterior chamber (at the start and at the end of the operation) had been taken. All samples were investigated for aerobe and anaerobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…In fact, the current culture media for isolating conjunctival bacteria described in Chapter 1 21 is different from that in the Khorazo et al studies 3 mentioned in Chapter 24 of the same volume, in the same book 21 (revised 10 years before). In more recent studies [25][26][27][28][29][30][31][32][33][34][35][36][37][38] most samples of patients undergoing cataract surgery have a small size and the frequency of the isolated bacteria varies a lot between them due to different factors 18 (the isolating culture media used, the exclusion criteria used to select the patients and the geographical area where they lived). Among these factors the climatic conditions in Madrid have been statistically associated with the conjunctival bacteria frequency of our patients undergoing cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the current culture media for isolating conjunctival bacteria described in Chapter 1 21 is different from that in the Khorazo et al studies 3 mentioned in Chapter 24 of the same volume, in the same book 21 (revised 10 years before). In more recent studies [25][26][27][28][29][30][31][32][33][34][35][36][37][38] most samples of patients undergoing cataract surgery have a small size and the frequency of the isolated bacteria varies a lot between them due to different factors 18 (the isolating culture media used, the exclusion criteria used to select the patients and the geographical area where they lived). Among these factors the climatic conditions in Madrid have been statistically associated with the conjunctival bacteria frequency of our patients undergoing cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Recently recommended preparations to reduce the risk of postoperative endophthalmitis in cataract surgery in clude antibiotics in the intraocular irrigating solution [ 13,14] and the routine use of povidone-iodine as a preopera- five disinfectant [15][16][17], Controversy remains over the use of antibiotics especially vancomycin, because of prob able adverse effects, the induction of vancomycin-resis tant bacteria, and financial limitations [18,19], To define the most appropriate preoperative preparation of the external eye against endophthalmitis, we evaluated the species and incidence of bacteria in the conjunctiva and lids which may gain access into the eye during cataract surgery [2][3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriological studies on the external eye have usually failed to record the presence of anaerobic bacteria [2,[5][6][7]20], However, using appropriate culture media and prop er anaerobic techniques, some reports have recently docu mented anaerobic bacteria as part of the normal conjunc tival flora [3,4,[14][15][16]21,22], and a cause of endophthal mitis [23][24][25][26], P. acnes is the most commonly isolated anaerobic bacterium, being found in 10-50% of conjunc tiva [21,22], In our study, P. acnes was obtained from the conjunctiva of 63 (12.9%) of 488 eyes undergoing cataract surgery. The spectrum and frequency of microorganisms in this study correspond with previous reports [14,22], Doyle et al [14] documented that culture from the con junctival sac showed coagulase-negative Staphylococcus in 70%, P. acnes in 47%, Staphylococcus aureus in 6%, and Corynebacterium in 6% of 17 patients ready for cata ract surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that bacterial contamination of the anterior chamber and the vitreous cavity during intraocular surgery is alarmingly frequent [6,13]. Accordingly, a number of ophthalmologists have suggested adding antibiotics to the irrigation or infusion fluid used for intraocular surgery.…”
Section: Discussionmentioning
confidence: 99%